Hydrograph rise times: progress report - Kar, Songthara Om, author; Colorado State University, Natural Resources Center, publisher (Colorado State University. Libraries, 1967)
An exploratory study on "Floods from Forest Compared to Those from Farmland" was performed as an extension of a thorough study of Hydrograph Rise Times (Appendix). Fifty-one watersheds were classified, using as a criterion the watershed coverage, into four groups: forest, cultivated, grass, and desert. Equations for predicting rise times and ten-year flood peaks were derived in simple and multiple regression analyses by computer. The best equations obtained were used to study the effects of changing the watershed coverage on rise times and flood peaks by using two average watersheds. However, no conclusions concerning the trend of behavior of watersheds compared are warranted. Detailed information on watershed coverage and condition must be secured before any further work is to be performed.
CER66-67SO61.
Part two is the author's thesis: Hydrograph rise times"--appendix.
Based on the author's thesis.
An interim report prepared for Office of Water Resources Research, U.S. Department of the Interior on the continuing investigation entitled: Floods from forest compared to those from farmland.
Keywords: Hydraulic structures; Runoff